Home Food Gardening: Benefits and Barriers During the COVID-19 Pandemic in Santiago, Chile - Cerda, Constanza; Guenat, Solène; Egerer, Monika; Fischer, Leonie K. (Frontiers in Sustainable Food Systems, 2022)
The recent COVID-19 pandemic changed the way people live in an unprecedented way. This includes severe impacts on people’s health and wellbeing such as stress, reduced physical activity, and loneliness due to confinement. In parallel, people had to find ways on how to secure their food, with fresh food especially scarce in some regions due to lock-downs and a limited flow of goods. As in previous massive crises, the practice of home food gardening seemed to have increased during this pandemic. Yet, it is largely unknown, which parts of society took to home food gardening, in which urban setting home food gardening was practiced, and to which extent this practice contributed to people’s daily livelihoods during the pandemic. Therefore, in this case study research, we explore (a) who practices home food gardening specifically, (b) the garden characteristics, and (c) the main perceived benefits and barriers bound to home food gardening during the pandemic. We set up an online questionnaire, targeted at the population of Santiago de Chile, for which we received 305 responses. Our results clearly show that the possibility of being in contact with nature and feeling less stress through practicing home food gardening were the most significant perceived benefits, while lack of or inadequate space to garden and limited knowledge on home food gardening were the main barriers. We also discovered a relationship between garden size and perceived benefits: the larger the garden, the stronger the agreement to the perceived benefits. These findings highlight for the specific context of a metropolitan region in South America that access to gardens and green space are a relevant topic if such practice is promoted, to contribute to a just way of living in cities. Likewise, the practice of home food gardening can be a relevant tool to cope with the adverse consequences of the pandemic by informing public initiatives to promote healthier lifestyles during this and future crises contexts and also in the awaited ‘ordinary’ times.